Modified graphite material, preparation method and application thereof and lithium ion battery

By modifying natural graphite with asphalt using a liquid phase system containing polymerization functional groups and granulating it with asphalt, the problem that modified graphite materials in the prior art cannot take into account both the magnification and circulation performance in lithium-ion batteries, achieving high performance and low performance Cost battery material.

CN119490183APending Publication Date: 2025-02-21NINGBO SHANSHAN NEW MATERIAL TECH
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411718026.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, modified graphite material after granulating natural graphite using asphalt is used as the negative electrode material in lithium-ion batteries, excellent rate performance and cycle performance cannot be taken into account, and the cost is high and the environmental pressure is high.

Method used

Using a liquid phase system containing polymerization functional groups as a modifier, natural graphite is modified and granulated with asphalt to form a solid bonding structure and a carbon layer with excellent conductivity, thereby improving the lithium-ion battery Magnification and cycling performance.

Benefits of technology

It achieves excellent rate performance and circulation performance of lithium-ion batteries, reduces asphalt usage and cost, reduces exhaust gas volume and environmental protection costs, and extends the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490183A_ABST
    Figure CN119490183A_ABST
Patent Text Reader

Abstract

The invention discloses a modified graphite material, a preparation method and application thereof and a lithium ion battery. The preparation method of the modified graphite material comprises the following steps: S1, carrying out first mixing on natural graphite and a modifier to obtain a first precursor; wherein the modifier is a liquid phase system containing polymerization reaction functional groups; s2, performing second mixing on the first precursor and asphalt, and performing granulation treatment on the mixture to obtain a second precursor; and S3, carrying out graphitization treatment on the second precursor to obtain the lithium ion battery positive electrode material. And the lithium ion battery obtained by taking the obtained modified graphite material as the negative electrode material has excellent rate capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified graphite material, a preparation method thereof, an application thereof and a lithium ion battery. Background Art

[0002] Natural graphite has high capacity and compaction density. In the application of HEV and power tools, natural graphite has the advantage of energy density. However, due to the different sizes of natural graphite particles, many surface defects, poor compatibility with electrolytes, many side reactions, and low cycle life, although natural graphite has the advantage of energy density, it needs to be designed and modified to achieve both excellent rate performance and cycle performance.

[0003] The prior art often uses mechanical crushing to reduce the size of flake graphite, and re-granulates it to improve the rate performance of natural graphite-based negative electrodes, and improves its rate and cycle life by coating the graphitized product after natural graphite and asphalt granulation with a layer of amorphous carbon. However, there is difficulty in secondary granulation of natural graphite after crushing, and a high proportion of asphalt needs to be added to complete the granulation process. The cost of asphalt is relatively high, which not only increases the cost of raw materials, but also generates a large amount of tail gas during the production process, affecting the operation and life of the equipment. At the same time, the tail gas generated puts great pressure on environmental protection and greatly increases the environmental protection cost. Even if the amount of asphalt is increased, when the resulting modified graphite material is used as a negative electrode material in lithium-ion batteries, lithium-ion batteries cannot take into account both excellent rate performance and cycle performance.

[0004] Chinese patent application CN109970052A uses small-particle natural graphite for secondary granulation. Although it improves the performance of graphite negative electrode materials, the capacity performance and cycle performance of the resulting lithium-ion battery are improved. However, even if the amount of asphalt is as high as 10%-20%, the cost of natural graphite modification becomes higher, and exhaust gas treatment becomes more difficult. The resulting lithium-ion battery cannot take into account both excellent rate performance and cycle performance.

[0005] Chinese patent application CN116443871A treats natural graphite with acid and mixes it with asphalt for granulation. Although the capacity performance and charge-discharge efficiency of lithium-ion batteries using the prepared graphite negative electrode material are good, the amount of asphalt used is as high as 18%-22%, and the resulting lithium-ion battery cannot take into account both excellent rate performance and cycle performance. Summary of the invention

[0006] In order to overcome the defect that the existing lithium ion battery using modified graphite material obtained by granulating natural graphite with asphalt as negative electrode material cannot take into account both excellent rate performance and cycle performance, the present invention provides a modified graphite material and its preparation method, application and lithium ion battery. When asphalt and a modifier are used to modify natural graphite in the preparation method of the modified graphite material of the present invention, the asphalt and natural graphite have strong adhesion and granulation is easier. When the obtained modified graphite material is used as a negative electrode material in a lithium ion battery, the obtained lithium ion battery can take into account both excellent rate performance and cycle performance.

[0007] To achieve the above objectives, the present invention adopts the following technical solutions.

[0008] The present invention provides a method for preparing a modified graphite material, which comprises the following steps:

[0009] S1. Mixing natural graphite and a modifier to obtain a first precursor; wherein the modifier is a liquid phase system containing a polymerization reaction functional group;

[0010] S2, performing a second mixing of the first precursor and asphalt, and granulating the mixture to obtain a second precursor;

[0011] S3, graphitizing the second precursor to obtain.

[0012] In the prior art, natural graphite is granulated by adding asphalt. Asphalt has a certain fluidity at high temperature, and coking reaction occurs between asphalt adsorbed on different natural graphite particles, so that different natural graphite particles are bonded together. However, the fluidity of asphalt at high temperature is limited, and it cannot enter the internal gaps and holes of natural graphite particles, so that the actual bonding force is not strong, and the modification effect is poor. When used as the negative electrode material of the battery, the natural graphite particles are easily broken due to the volume shrinkage during the battery cycle, which further exposes the surface defects of the particles and causes side reactions in the electrolyte, reducing the cycle life.

[0013] The modified graphite material of the present invention is specially designed to use a liquid phase system containing a polymerization reaction functional group as a modifier, which has good wettability to natural graphite particles and can easily enter the internal pores and holes of natural graphite particles. The coking reaction can occur inside the natural graphite particles to form a strong bonding structure, thereby improving the cycle life of the lithium ion battery obtained by using the modified graphite material as the negative electrode material. At the same time, after graphitization, the internal bonding structure forms a carbon layer with excellent conductive performance, thereby improving the rate performance of the lithium ion battery obtained by using the modified graphite material as the negative electrode material.

[0014] In step S1, the liquid phase system containing polymerization reaction functional groups preferably includes a polymer containing polymerization reaction functional groups and a solvent.

[0015] The polymer containing polymerization reaction functional groups preferably includes one or more of polyacrylic acid compounds, polyacrylate compounds, styrene-butadiene rubber, polyacrylonitrile, polyurethane, polyvinyl acetate, sodium carboxymethyl cellulose, polyvinyl alcohol and sodium alginate.

[0016] Wherein, the solvent is preferably water; further, the liquid phase system containing polymerization reaction functional groups is preferably an aqueous solution or emulsion containing polymerization reaction functional groups.

[0017] In some preferred embodiments, the liquid phase system containing polymerization reaction functional groups is an emulsion containing polymerization reaction functional groups, wherein the polymer containing polymerization reaction functional groups is one or more of polyacrylic acid compounds, polyacrylate compounds, styrene-butadiene rubber (SBR), polyacrylonitrile, polyurethane and polyvinyl acetate.

[0018] In other preferred embodiments, the liquid phase system containing polymerization reaction functional groups is an aqueous solution containing polymerization reaction functional groups, and the polymer containing polymerization reaction functional groups is sodium carboxymethyl cellulose (CMC), polyvinyl alcohol and sodium alginate (SA).

[0019] In step S1, the natural graphite may be natural graphite conventionally used in the art, preferably including flake graphite and / or block graphite.

[0020] In step S1, the Dv50 particle size of the natural graphite is preferably 4-20 μm, for example, 8.0 μm.

[0021] In step S1, the mass ratio of the natural graphite to the modifier is preferably (0.9-99):1, more preferably (4-99):1, for example, 9:1 or 11.5:1.

[0022] In step S1, the solid content of the modifier in the first precursor is preferably 1%-20%, for example 2%, 4% or 8%, where the percentage is the mass of the solid component of the modifier in the first precursor relative to the total mass of the first precursor.

[0023] In step S1, the solid content of the modifier is 4%-50%, for example, 40%, where the percentage is the percentage of the mass of the solid component in the modifier to the total mass of the modifier.

[0024] In step S1, the first mixing is preferably performed in a liquid phase coating device. The liquid phase coating device can be a conventional liquid phase coating device in the art, preferably a fusion machine.

[0025] In step S2, the asphalt may be asphalt conventionally used in the art, preferably one or more of petroleum asphalt, natural asphalt and coal tar asphalt. The asphalt may also be preferably modified asphalt. The modified asphalt refers to an asphalt binder obtained by modifying one or more of petroleum asphalt, natural asphalt and coal tar asphalt.

[0026] In step S2, the mass ratio of the first precursor to asphalt is (4-19):1, for example, 5.7:1 or 9:1.

[0027] In step S2, the Dv50 particle size of the asphalt is preferably 3-20 μm, for example, 8.0 μm.

[0028] In step S2, the content of the asphalt in the second precursor is preferably 5%-35%, for example, 10%, 15% or 20%, where the percentage is the mass of the asphalt relative to the total mass of the second precursor.

[0029] In step S2, the second mixing is preferably performed in a mixing device. The mixing device may be a conventional mixing device in the art, such as a ribbon mixer.

[0030] In step S2, the mass ratio of the natural graphite in the first precursor to the asphalt is preferably (1.5-19):1, for example, 4:1, 4.5:1, 6:1, 9:1, 9.6:1, 18:1 or 18.4:1.

[0031] In step S2, the granulation process can be a granulation process conventionally performed in the art. The granulation process is generally performed under the protection of an inert gas.

[0032] In step S2, the temperature of the granulation treatment is preferably above 300°C, more preferably 300-700°C, further more preferably 500-700°C, for example 600°C.

[0033] In step S2, the granulation treatment time is preferably 2-8 hours, for example 6 hours.

[0034] In the granulation process, the modifier participates in the asphalt coking reaction under high temperature, reduces the interface resistance between asphalt and natural graphite particles, forms a strong chemical bond, and plays the role of a binder, thereby facilitating the granulation of natural graphite.

[0035] In step S2, the Dv50 particle size of the second precursor is preferably 4-20 μm, for example, 13.0-15.0 μm.

[0036] In step S3, the temperature of the graphitization treatment is preferably 2500-3000°C, for example 2800°C.

[0037] In step S3, the graphitization treatment time is preferably 20-60 h, for example 48 h.

[0038] In step S3, the graphitization equipment for the graphitization treatment may be a graphitization equipment conventionally used in the art, such as an Acheson graphitization furnace or a box-type graphitization furnace.

[0039] The present invention provides a modified graphite material prepared by adopting the preparation method of the modified graphite material.

[0040] The present invention provides a modified graphite material, which comprises a first graphite and a second graphite, wherein the first graphite is natural graphite, and the second graphite is distributed in the internal voids of the particles of the first graphite and in the intergranular spaces of the first graphite.

[0041] In the present invention, the "internal voids of the particles" of the first graphite refer to the openings inside a single particle of the first graphite, and the "interparticle gaps" of the first graphite refer to the gaps between two adjacent particles of the first graphite. The second graphite is distributed in the internal voids and interparticle gaps of the first graphite particles. On the one hand, a strong bonding structure can be formed between the particles of the first graphite, thereby improving the cycle life of the material; on the other hand, a carbon layer with excellent electrical conductivity can be formed between the particles of the first graphite, thereby improving the rate performance of the material.

[0042] Wherein, the natural graphite is preferably flake graphite and / or block graphite.

[0043] Wherein, the mass ratio of the first graphite to the second graphite is preferably (4-19):1.

[0044] The present invention provides an application of the modified graphite material as described above as a negative electrode material in a lithium ion battery.

[0045] The present invention also provides a lithium ion battery using the modified graphite material.

[0046] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0047] The reagents and raw materials used in the present invention are commercially available.

[0048] The positive and progressive effects of the present invention are:

[0049] 1. In the preparation method of the modified graphite material of the present invention, natural graphite is modified by using a specific modifier. The modified natural graphite has a strong bonding force when granulated with asphalt, so that the composite particles after granulation are more tightly combined, the asphalt coating is more uniform, and the electron transmission capacity between particles is increased; when the obtained modified graphite material is used as a negative electrode material in a lithium ion battery, the obtained lithium ion battery can have both excellent rate performance and cycle performance.

[0050] 2. Furthermore, the composite particles in the obtained modified graphite material are more tightly bound, so that the amount of asphalt used in the preparation method of the present invention can be greatly reduced, and the source of the modifier is wide and the price is low, thereby reducing the overall granulation cost.

[0051] 3. At the same time, the amount of exhaust gas is greatly reduced, which reduces environmental protection costs, equipment maintenance costs, and extends the service life of equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a schematic diagram of the structure of the modified graphite material obtained in Comparative Example 1.

[0053] Figure 2 Schematic diagram of the structure of the modified graphite material obtained in Examples 1-7.

[0054] Figure 3 The graph is a test chart of the cycle performance of lithium-ion batteries made using the modified graphite materials in Examples 1-7 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0055] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0056] The main reagents used in the following examples and comparative examples are as follows:

[0057] Polymethyl methacrylate emulsion was purchased from Sichuan Yindi Le Materials, model LA136D;

[0058] CMC glue was purchased from Daicel, Japan, model number is CMC2200;

[0059] SBR emulsion Japanese JSR, model is JSR TRD104A;

[0060] Flake graphite was purchased from Qingdao Huateng Graphite, model SG-8;

[0061] The modified asphalt was purchased from Liaoning Runxing New Materials, model number 250#.

[0062] Example 1

[0063] (1) Preparation of modified graphite materials:

[0064] S0, shaping the flake graphite with a size smaller than 100 mesh into flake graphite powder with a D50 particle size of 8.0 μm;

[0065] S1, then mixing the flake graphite powder and polymethyl methacrylate emulsion (solid content of 40%) at a mass ratio of 90:10 (a total of 100 parts by mass) in a fusion machine at room temperature to obtain a first precursor (wherein the content of the modifier solid component is 4%);

[0066] S2-1, mixing the first precursor and modified asphalt (D50 particle size: 8 μm) in a ribbon mixer at a mass ratio of 95:5 (100 parts by mass in total) to obtain a mixture; wherein the mass ratio of flake graphite powder to modified asphalt is 18:1;

[0067] S2-2, the mixed material is subjected to heat treatment at 600° C. for 6 hours in a horizontal kettle low-temperature heat treatment equipment under the protection of inert gas to obtain a second precursor (D50 particle size is 13.0-15.0 μm);

[0068] S3. Using a box-type graphitization furnace, graphitize the second precursor at 2800° C. for 48 hours to obtain a modified graphite material.

[0069] (2) Preparation of lithium-ion batteries:

[0070] Preparation of negative electrode slurry: dissolving binders CMC and SBR in water to obtain a negative electrode binder gel (the mass ratio of CMC to SBR is 1.2:1, and the mass percentage of CMC in the negative electrode binder gel is 4%); mixing the modified graphite material, the conductive agent SP and the negative electrode binder gel according to the mass ratio of the modified graphite material, the conductive agent SP and the binder (CMC+SBR) of 93:3:4 (a total of 100 parts by mass) to obtain a negative electrode slurry;

[0071] Preparation of positive electrode slurry: dissolving the binder PVDF in NMP to obtain a positive electrode binder glue (solid content of 12%); mixing LiFePO4, conductive agent SP and positive electrode binder glue according to LiFePO4, conductive agent SP and binder PVDF = 92:5:3 (a total of 100 parts by mass) to obtain a positive electrode slurry;

[0072] Preparation of positive and negative electrode sheets: The positive electrode slurry is coated on the aluminum foil, and the required positive electrode sheet is prepared by rolling, baking and slicing processes; the negative electrode slurry is coated on the copper foil, and the required negative electrode sheet is prepared by rolling, baking and slicing processes.

[0073] Lithium battery assembly and preparation: The positive and negative electrode sheets and separator (12 μm PP separator) are stacked, welded, and packaged with aluminum-plastic film to obtain the required soft-pack lithium-ion battery; the assembled soft-pack lithium-ion battery is baked, filled with electrolyte, formed, and divided into different volumes to obtain a lithium-ion battery with a rated capacity of 5Ah. The electrolyte was purchased from Shenzhen Xinzhoubang Technology Co., Ltd., model LBC338G74.

[0074] Example 2

[0075] The only difference between Example 2 and Example 1 is that in step S1, the mass ratio of flake graphite powder to polymethyl methacrylate emulsion (solid content of 40%) is 80:20, the content of the solid component of the modifier in the obtained first precursor is 8%, and the mass ratio of flake graphite powder to modified asphalt is 4:1; the other conditions remain consistent with Example 1.

[0076] Example 3

[0077] The only difference between Example 3 and Example 1 is that in step S1, the modifier is CMC glue (solid content is 4%), the mass ratio of flake graphite powder to CMC glue is 48:52, the content of the solid component of the modifier in the obtained first precursor is 4%, and the mass ratio of flake graphite powder to modified asphalt is 9.6:1; the other conditions remain the same as in Example 1.

[0078] Example 4

[0079] The only difference between Example 4 and Example 1 is that in step S1, the modifier is SBR emulsion (solid content is 50%), the mass ratio of flake graphite powder to SBR emulsion is 92:8, the content of the solid component of the modifier in the obtained first precursor is 4%, and the mass ratio of flake graphite powder to modified asphalt is 18.4:1; the other conditions remain consistent with Example 1.

[0080] Example 5

[0081] The only difference between Example 5 and Example 1 is that in step S2-1, the mass ratio of the first precursor to the modified asphalt is 80:20 (100 parts by mass in total), and the mass ratio of the flake graphite powder to the modified asphalt is 4.5:1; the other conditions remain the same as in Example 1.

[0082] Example 6

[0083] The only difference between Example 6 and Example 1 is that in step S2-1, the mass ratio of the first precursor to the modified asphalt is 85:15 (100 parts by mass in total), and the mass ratio of the flake graphite powder to the modified asphalt is 6:1; the other conditions remain the same as in Example 1.

[0084] Example 7

[0085] The only difference between Example 7 and Example 1 is that in step S2-1, the mass ratio of the first precursor to the modified asphalt is 90:10 (100 parts by mass in total), and the mass ratio of the flake graphite powder to the modified asphalt is 9:1; the other conditions remain the same as in Example 1.

[0086] The structural schematic diagram of the modified graphite material obtained in Examples 1-7 is as follows: Figure 2 shown.

[0087] Comparative Example 1

[0088] The modified graphite material in Comparative Example 1 was prepared by the following steps:

[0089] 1. Shape the flake graphite with a size less than 100 mesh into flake graphite powder with a D50 particle size of 8.0 μm;

[0090] 2. Mix the flake graphite powder and modified asphalt (D50 8 μm) in a mass ratio of 95:5 (100 parts by mass in total) to obtain a mixture;

[0091] 4. The mixture is heat treated at 600°C for 6 hours in a horizontal kettle low-temperature heat treatment equipment under the protection of inert gas to obtain a precursor;

[0092] 5. Graphitize the precursor at 2800°C for 48 hours to obtain a modified graphite material. The structural schematic diagram of the obtained modified graphite material is as follows: Figure 1 shown.

[0093] Comparative Example 2

[0094] 1. Shape the flake graphite with a size less than 100 mesh into flake graphite powder with a D50 particle size of 8.0 μm;

[0095] 2. Then, the flake graphite powder, the modifier polymethyl methacrylate emulsion (solid content of 40%) and the modified asphalt are mixed in a fusion machine to obtain a first precursor, and the mass ratio of the flake graphite powder, the modifier and the modified asphalt is 89.3:3.7:7 (a total of 100 parts by mass);

[0096] 3. The first precursor is heat treated at 600° C. for 6 hours in a horizontal kettle low-temperature heat treatment equipment under the protection of inert gas to obtain a second precursor;

[0097] 5. Graphitize the second precursor at 2800° C. for 48 hours to obtain a modified graphite material.

[0098] Effect Example 1

[0099] The rate performance and cycle performance of the lithium ion batteries obtained in Examples 1-7 and Comparative Examples 1-2 were tested:

[0100] (1) Rate performance of lithium-ion batteries

[0101] Test conditions: In a 25°C constant temperature box, charge at 0.5C and discharge at different rates (1C, 5C, 10C, 15C and 20C). The test results are shown in Table 1.

[0102] (2) Cycle performance of lithium-ion batteries

[0103] Test conditions: at room temperature, 0.5C charging, 5C discharging, voltage range 2.2V~3.4V, 300 cycles. Test results are shown in Table 2 and Figure 3 shown.

[0104]

[0105]

[0106] According to Table 1 and Table 2, the capacity retention rate of the lithium ion batteries obtained in Examples 1-7 of the present invention at a discharge rate of 5C can reach more than 93%, the capacity retention rate at a discharge rate of 10C can reach more than 71%, the capacity retention rate at a discharge rate of 15C can reach more than 45%, the capacity retention rate at a discharge rate of 20C can reach more than 30%, and the capacity retention rate at 300 cycles can reach more than 80%. The obtained lithium ion batteries can take into account both excellent rate performance and cycle performance.

[0107] Compared with Example 1, no modifier was used in Comparative Example 1, but asphalt and flake graphite were directly mixed. The capacity retention rate of the lithium-ion battery obtained by using the modified graphite material as the negative electrode material was significantly deteriorated at discharge rates of 5C, 10C, 15C and 20C, and the capacity retention rate was also greatly reduced after 300 cycles, and it was impossible to take into account both excellent rate performance and cycle performance.

[0108] Compared with Example 1, in Comparative Example 2, natural graphite, modifier and asphalt are directly mixed in one step. The capacity retention rate of the lithium-ion battery obtained by using the modified graphite material as the negative electrode material is significantly reduced at discharge rates of 5C, 10C, 15C and 20C, and the capacity retention rate is also significantly deteriorated after 300 cycles, and it is impossible to take into account both excellent rate performance and cycle performance.

[0109] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified graphite material, characterized in that: It includes the following steps: S1. Mixing natural graphite and a modifier to obtain a first precursor; wherein the modifier is a liquid phase system containing a polymerization reaction functional group; S2, performing a second mixing of the first precursor and asphalt, and granulating the mixture to obtain a second precursor; S3, graphitizing the second precursor to obtain.

2. The method for preparing the modified graphite material according to claim 1, characterized in that: In step S1, the liquid phase system containing polymerization reaction functional groups includes a polymer containing polymerization reaction functional groups and a solvent; Wherein, the polymer containing polymerization reaction functional groups preferably includes one or more of polyacrylic acid compounds, polyacrylate compounds, styrene-butadiene rubber, polyacrylonitrile, polyurethane, polyvinyl acetate, sodium carboxymethyl cellulose, polyvinyl alcohol and sodium alginate; Wherein, the solvent is preferably water; further, the liquid phase system containing polymerization reaction functional groups is preferably an aqueous solution or emulsion containing polymerization reaction functional groups; More preferably, the liquid phase system containing polymerization reaction functional groups is an emulsion containing polymerization reaction functional groups, wherein the polymer containing polymerization reaction functional groups is one or more of polyacrylic acid compounds, polyacrylate compounds, styrene-butadiene rubber, polyacrylonitrile, polyurethane and polyvinyl acetate; More preferably, the liquid phase system containing polymerization reaction functional groups is an aqueous solution containing polymerization reaction functional groups, wherein the polymer containing polymerization reaction functional groups is sodium carboxymethyl cellulose, polyvinyl alcohol and sodium alginate.

3. The method for preparing the modified graphite material according to claim 1, characterized in that: Step S1 satisfies one or more of the following conditions af: a. The natural graphite includes flake graphite and / or block graphite; b. The Dv50 particle size of the natural graphite is 4-20 μm, for example, 8.0 μm; c. The solid content of the modifier in the first precursor is 1%-20%, for example, 2%, 4% or 8%, where the percentage is the mass of the solid component of the modifier in the first precursor to the total mass of the first precursor; d. The solid content of the modifier is 4%-50%, for example, 40%, where the percentage is the percentage of the mass of the solid component in the modifier to the total mass of the modifier; e. The mass ratio of the natural graphite to the modifier is (0.9-99):1, preferably (4-99):1, for example 9:1 or 11.5:1; f. The first mixing is carried out in a liquid phase coating device; the liquid phase coating device is, for example, a fusion machine.

4. The method for preparing the modified graphite material according to claim 1, characterized in that: Step S2 satisfies one or more of the following conditions aj: a. The asphalt is one or more of petroleum asphalt, modified asphalt, natural asphalt and coal tar asphalt, for example, modified asphalt; b. The Dv50 particle size of the asphalt is 3-20 μm, for example, 8.0 μm; c. The mass ratio of the natural graphite in the first precursor to the asphalt is (1.5-19):1, for example, 4:1, 4.5:1, 6:1, 9:1, 9.6:1, 18:1 or 18.4:1; d. The mass ratio of the first precursor to asphalt is (4-19):1, for example, 5.7:1 or 9:1; e. In the second precursor, the content of the asphalt is 5%-35%, for example, 10%, 15% or 20%, where the percentage is the mass of the asphalt relative to the total mass of the second precursor; f. The second mixing is carried out in a ribbon mixer; g. The granulation process is carried out under the protection of an inert gas; h. The temperature of the granulation treatment is above 300° C., preferably 300-700° C., more preferably 500-700° C., for example 600° C.; i. The granulation treatment time is 2-8 hours, for example 6 hours; j. The Dv50 particle size of the second precursor is 4-20 μm, for example, 13.0-15.0 μm.

5. The method for preparing the modified graphite material according to claim 1, characterized in that: In step S3, the graphitization treatment satisfies one or more of the following conditions ac: a. The temperature of the graphitization treatment is 2500-3000°C, for example, 2800°C; b. The graphitization treatment time is 20-60 h, for example, 48 h; c. The graphitization equipment for the graphitization treatment is an Acheson graphitization furnace or a box-type graphitization furnace.

6. A modified graphite material, characterized in that: The modified graphite material is prepared by the method for preparing the modified graphite material according to any one of claims 1 to 5.

7. A modified graphite material, characterized in that: The invention comprises a first graphite and a second graphite, wherein the first graphite is natural graphite, and the second graphite is distributed in the internal voids of the particles of the first graphite and in the intergranular spaces of the first graphite.

8. The modified graphite material according to claim 7, characterized in that It satisfies one or both of the following conditions ab: a. The natural graphite includes flake graphite and / or block graphite; b. The mass ratio of the first graphite to the second graphite is (4-19):

1.

9. Use of the modified graphite material as claimed in any one of claims 6 to 8 as a negative electrode material in a lithium ion battery.

10. A lithium ion battery, characterized in that: It comprises the modified graphite material as claimed in any one of claims 6 to 8.

Citation Information

Patent Citations

  • Natural graphite granulation and secondary coating modification method

    CN109970052A

  • Processing technology of graphite negative electrode material

    CN116443871A

  • Lithium ion power battery composite cathode material and its preparation method

    CN103078090A

  • Modified natural graphite and preparation method thereof

    CN104037417A

  • Graphite negative electrode material of lithium ion battery and preparation method for graphite negative electrode material

    CN104425822A